2011
DOI: 10.1007/s00595-010-4397-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of excess body weight on the surgical outcomes of total gastrectomy

Abstract: Although TG for gastric cancer is technically more difficult in overweight patients, they should not be denied this operation. Conversely, we should make a greater effort to improve the surgical outcomes of overweight patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 33 publications
(29 reference statements)
2
21
2
1
Order By: Relevance
“…18 In contrast, studies in patients after TG showed that an increased BMI was associated with greater blood loss, longer operation times, and increased rate of postoperative morbidity. 19,20 Although all of these studies used BMI alone without measurement of VFA as a parameter for obesity, results in these studies support our findings above. We consider that visceral fat is likely to have crucial influence on operative procedures during TG rather than DG.…”
supporting
confidence: 82%
“…18 In contrast, studies in patients after TG showed that an increased BMI was associated with greater blood loss, longer operation times, and increased rate of postoperative morbidity. 19,20 Although all of these studies used BMI alone without measurement of VFA as a parameter for obesity, results in these studies support our findings above. We consider that visceral fat is likely to have crucial influence on operative procedures during TG rather than DG.…”
supporting
confidence: 82%
“…In addition, Dhar et al [17] suggested that a higher BMI is closely related to disease recurrence after gastric cancer surgery because of difficulties in dissecting lymph nodes in obese patients. In our report, there were 41 overweight and 54 nonoverweight patients; there were many more overweight patients than in Nobuoka's study (84.6% vs. 15.46%, respectively) [30]. Thus, there may be selection bias effects of too many overweight patients in our study.…”
Section: Discussionmentioning
confidence: 60%
“…The exact cause was not disclosed in our study. However, Nobuoka et al [30] reported the operating times were longer in the overweight group. In addition, Dhar et al [17] suggested that a higher BMI is closely related to disease recurrence after gastric cancer surgery because of difficulties in dissecting lymph nodes in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Overall operative time was included in the majority of studies and was the only reported outcome that was associated with obesity in a majority of publications (Table ) . Among the 70 studies that included operative time as an outcome metric, 42 (60%) reported that obesity was associated with a longer operative time …”
Section: Resultsmentioning
confidence: 99%
“…For example, in one study the increase in operative time for each 1 unit of increase in BMI was only 2 min per case . In another study, while the operative time among obese patients was longer, the average difference was only about 20 min in obese versus non‐obese patients . While operative time may affect health care costs, the relation of modest increases in operative time with patient and hospital outcomes needs to be further defined.…”
Section: Discussionmentioning
confidence: 99%